2016
DOI: 10.1111/and.12670
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction in Klinefelter's syndrome patients

Abstract: Klinefelter's syndrome (KS) is the most common chromosomal abnormality in men with infertility and hypogonadism. Although its influence on fertility has been extensively investigated, very few studies assessed the sexual function of patients with KS. Our aim was to assess the prevalence of sexual dysfunction in patients with KS and investigate possible aetiological factors for reported findings. Medical records of 53 patients with KS were retrospectively reviewed and compared to 75 age-matched control subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…Yoshida found that 67.5% of subjects with KS have at least one sexual function disturbance [ 30 ]. In our study we found a prevalence of ED among patients with KS of 21.1%, which is comparable with previous literature regarding the prevalence of ED in KS [ 31 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Yoshida found that 67.5% of subjects with KS have at least one sexual function disturbance [ 30 ]. In our study we found a prevalence of ED among patients with KS of 21.1%, which is comparable with previous literature regarding the prevalence of ED in KS [ 31 ].…”
Section: Discussionsupporting
confidence: 91%
“…This means that erectile function and desire are covariates negatively associated with E2/T and that low desire and ED may influence each other in patients with KS. In fact, these results are similar to those by El Bardisi et al, who found a significantly higher incidence of low libido in KS patients vs. controls (54.7% vs. 17.3%, respectively) despite normal testosterone levels [ 31 ].…”
Section: Discussionsupporting
confidence: 90%
“…Epidemiological studies of EjDs among infertile men are limited. Currently, three case-control studies 5 , 19 , 60 and six single-arm studies 17 , 22 , 40 , 61 , 62 , 63 have investigated PE among infertile men; one case-control 64 and one single-arm study 65 have looked at RE, while only one study have investigated the prevalence of anejaculation among infertile men 10 ( Table 3 ).…”
Section: Remarksmentioning
confidence: 99%
“…The strength of our study is related to the combined, medical (including biochemical, hormonal, and P‐CDU) and psychosexological, approach and to the evaluation of sexual function at baseline and after T replacement therapy. The percentage of ED among our KS cohort (14/62, 22.6%) is absolutely comparable to that found by Corona (5/23, 21.7%) (Corona et al ., ) and El Bardisi (10/53, 18.9%) (El Bardisi et al ., ). The prevalence of PE and DE was also similar between our study and that of Corona, but lower than that found by El Bardisi (22.6% of PE).…”
Section: Discussionmentioning
confidence: 97%
“…Yoshida found that 67.5% of KS subjects showed a disturbance in their sexual function, a prevalence however not different from a control group (Yoshida et al ., ). More recent studies showed that KS is associated with hypersexuality, paraphilic behaviors, and gender dysphoria, mediated by obsessive–compulsive and autistic traits (Fisher et al ., ), and with significant lower libido and incidence of premature ejaculation with respect to controls (El Bardisi et al ., ). The role of T levels and hypogonadism in sexual dysfunction of KS subjects has been poorly defined.…”
Section: Introductionmentioning
confidence: 97%